Engineering molecular chains in carbon nanotubes - Chamberlain, Thomas W. (2012)
A range of mono- and bis-functionalised fullerenes have been synthesised and inserted into single-walled carbon nanotubes. The effect of the size and shape of the functional groups of the fullerenes on the resultant 1D arrays formed within the nanotubes was investigated by high resolution transmission electron microscopy and X-ray diffraction. The addition of non-planar, sterically bulky chains to the fullerene cage results in highly ordered 1D structures in which the fullerenes are evenly spaced along the internal nanotube cavity. Theoretical calculations reveal that the functional groups interact with neighbouring fullerene cages to space the fullerenes evenly within the confines of the nanotube. The addition of two functional groups to opposite sides of the fullerene cages results in a further increase in the separation of the fullerene cages within the nanotubes at the cost of lower nanotube filling rates.